Community-Based Tourism Route Development, Bang Klam District, Songkhla Province - Yukhong, Chatthida; Chonphacha, Sakkarin (JOURNAL OF SOUTHERN TECHNOLOGY, 2023)
The development of community-based tourism routes is part of activities to help increase and generate sustainable incomes for the community. The purpose of this study is to develop community-based creative tourist attraction routes. The study employed a participatory action research design conducted in Mae Tom and Bang Klam Sub-Districts, Bang Klam District, Songkhla Province. A sample of 30 individuals including chief executive of local Sub-District Administrative Organizations, relevant developers, and stakeholders, tourism and marketing experts participated in the study. They were selected using purposive sampling. Research tools are 1) in-depth interview questions, 2) a focus group discussion form, 3) a participant observation form, and 4) a tourism route development plan. Data were analyzed using content analysis and results were presented descriptively. It was revealed that the three major contextual factors which contribute to the strengths in developing new tourism routes are natural resources, green agriculture, and community wisdom. A one-day community-based tourism can be created based on these strengths in two routes. Route 1 could highlight natural and green tourism that covers Suan Pansuk - Phirom Farm - Suan Lung Rom - Morrakot Pool - Bang Klam Floating Market. Route 2 can be for community wisdom tourism which convers places from Wat Khu Tao - Moral Herbal Community Enterprise - Toei Panan Basketry Community Enterprise - Bangklampottery -Wat Khu Tao to Prachuap Silp Manora Training Center. Sustainable income generation and self-reliance of the people conceives through activities related to tourism management, e.g., community tour agents, local taxi services, food preparation for tourists, and community product distribution. Findings of this study have been applied to promote tourism and contribute to the body of knowledge for students and general public as well as generating activities and incomes for the community.